Comparison of growth factor adsorbed scaffold and conventional scaffold with growth factor supplemented media for primary human articular chondrocyte 3D culture - Jeerawan Klangjorhor (2018)
© 2014 Klangjorhor et al. Background: Cartilage tissue engineering offers new strategies in repairing damaged cartilage. Scaffolds have been used for the in vitro and in vivo procedures for this application, which demonstrates the compatible biological and physical properties that mimic natural tissues. Several types of scaffolds were used and had different effects on cell functions. The study was designed to develop a functional gelatin scaffold by adsorption of hyaluronan (HA) and the transforming growth factor ß3 (TGF-ß3) in a commercially available gelatin scaffold. Results: The biological properties of human articular chondrocytes were investigated during a 21-day cultivation embedded in either HA + TGF-ß3 adsorbed scaffolds or the conventional supplemented method. The rising of proliferation of chondrocytes embedded in adsorbed scaffolds was observed at day 17 and 21 of cultivation (1.27 and 1.28 fold, respectively). The chondrogenic gene expression of the chondrocytes embedded in HA + TGF-ß3 adsorbed scaffolds significantly increased: SOX-9 (1.65 fold), ACAN (7.65 fold) and COL2A1 (1.83 fold). Remarkably, over the 21 days of cultivation, HA + TGF-ß3 adsorbed scaffolds promoted the extracellular matrix molecules production with higher accumulation of HA (1.2 fold), collagen (1.42 fold) and uronic acid (1.41 fold). Moreover, the cell population and extracellular matrix production, which were examined by a histological analysis and a scanning electron microscope, were correlated with the biochemical analysis. Conclusion: A small amount of HA and TGF-ß3 initially adsorbed in the scaffolds (70 μg and 10 ng, respectively) was consumed over the 21-day cultivation. The HA + TGF-ß3 adsorbed gelatin scaffold is effective and more suitable than the conventional supplemented method for the in vitro assessment of human chondrocyte 3D culture.